2017
DOI: 10.1016/j.compositesa.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal and electromagnetic properties of nanographite platelets modified cementitious composites

Abstract: Nanographite platelets (NGPs) are used as multi-functional fillers to develop cementitious composites because the unique carbon-carbon hexagonal plane structure makes NGPs have excellent mechanical, electrical, dielectric and thermal properties. In this paper, cementitious composites filled with NGPs are fabricated to investigate the effect of NGPs on mechanical, thermal and electromagnetic properties of cementitious composites. Experiment results show that the addition of NGPs can effectively modify the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 41 publications
(40 reference statements)
1
24
0
1
Order By: Relevance
“…SEM images of cementitious composites filled with (a) 0 vol.% GNP, (b) 1 vol.% GNP, and (c) 5 vol.% GNP 70. GNP: graphene nanoplatelet.…”
mentioning
confidence: 99%
“…SEM images of cementitious composites filled with (a) 0 vol.% GNP, (b) 1 vol.% GNP, and (c) 5 vol.% GNP 70. GNP: graphene nanoplatelet.…”
mentioning
confidence: 99%
“…20 The addition of multifunctional core-shell multifunctional nano-particles into the composite materials showed signi顒僣ant improvements in the properties such as anti-corrosion, enhanced surface chemistry, electromagnetic resistance, and microwave absorption. 21 Cui et al 22 conducted a study on multifunctional cementitious materials by emphasizing the structural functions such as mechanical, electromagnetic, and thermal properties, modi顒僥d by nano-graphite platelets.…”
Section: Related Workmentioning
confidence: 99%
“…Koratkar et al [176] observed that the addition of carbon nanotubes can improve the damping ratio of concrete by 200% compared to the plain concrete. Wang et al [177] reported that the vibration damping ability of concrete can be increased by adding silica fume into concrete. Concrete will reduce the damping ability by adding coarse aggregate or fine aggregate.…”
Section: Self-damping Concretementioning
confidence: 99%